Three-dimensional localization and tracking of chromosomal loci throughout the Escherichia coli cell cycle - Karempudi, Praneeth; Gras, Konrad; Amselem, Elias; Zikrin, Spartak; Schirman, Dvir; Elf, Johan (Uppsala University, 2024)
The intracellular position of genes may impact their expression, but it has not been possible to accurately measure the 3D position of chromosomal loci. In 2D, loci can be tracked using arrays of DNA-binding sites for transcription factors (TFs) fused with fluorescent proteins. However, the same 2D data can result from different 3D trajectories. Here, we have developed a deep learning method for super-resolved astigmatism-based 3D localization of chromosomal loci in live E. coli cells which enables a precision better than 61 nm at a signal-to-background ratio of ~4 on a heterogeneous cell background. Determining the spatial localization of chromosomal loci, we find that some loci are at the periphery of the nucleoid for large parts of the cell cycle. Analyses of individual trajectories reveal that these loci are subdiffusive both longitudinally (x) and radially (r), but that individual loci explore the full radial width on a minute time scale.

This dataset contains the raw data, analysis and code needed to generate the figures presented in the paper. The raw data consists of microscopy images. The analysis and code consists of analysis code, output from the analysis and its post-processing.

Experimental data, analysis and plot scripts are all organized using unique IDs (UID; seen for example in the filenames of experimental data below). The README.txt file in the Analysis_of_data folder describes which UIDs for data, analysis & figure generation to combine for specific figures/tables.

For the microscopy experiments (has the prefix Microscopy_Data_ in their filenames) there is information on the growth condition, strain genotypes, which positions corresponds to which genotype, and also which figure the data was used in. All experiments were performed at 30 degrees Celsius.

Details on the output from microscopy experiments can be found in the file MicroscopyInformation.txt.
Keywords: Systems biology; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi